Revalidation of a moray eel, Gymnothorax mucifer Snyder, 1904 (Teleostei: Anguilliformes: Muraenidae), with a revised distribution - Huang, Wen-Chien; Chen, Hong-Ming; Liao, Te-Yu (Zootaxa, 2019)
Gymnothorax mucifer Snyder, 1904 has been synonymized with G. kidako (Temminck & Schlegel, 1846) since 2000. Examination of material from Hawaii (type locality) and Taiwan reveal that G. mucifer is a valid species based on morphological and molecular data. It can be distinguished from G. kidako by a plainly colored lower jaw (vs. mottled), white margin of the anal fin replaced by serial pale blotches posteriorly on the tail (vs. white margin continuous to tip of tail), more dentary teeth (17–27 vs. 16–20), and fewer total vertebrae (130–141 vs. 140–143). In the present study, a redescription of G. mucifer is provided, and the distribution of G. mucifer and G. kidako is reevaluated.